A Study on the Relationship Between Screen Usage Duration and Night-Time Eating in Young Adults - Sharma Anshu; Singh Karuna; Rikhari Aditi; Akansha; Jain Divita (BIO Web of Conferences)
The widespread use of digital devices has significantly impacted lifestyle behaviours in young adults, particularly dietary patterns and sleep cycles. This study aimed to assess the association between screen time, night-time eating behaviour, and body composition among young adults aged 18–25 years. A cross-sectional study was conducted with 150 students from Sharda University. Data were collected through a validated self-administered questionnaire, Food Frequency Questionnaire (FFQ), 24-hour dietary recall, and Bioelectrical Impedance Analysis (BIA). Statistical analysis was performed using SPSS v25.0, with chi-square tests applied to identify significant associations (p < 0.05). A total of 59.3% of participants reported using screens for more than four hours daily, while 81.3% engaged in food consumption after 8 PM at least once per week. Significant associations were observed between prolonged screen time and night-time eating, as well as screen use immediately before bedtime. Participants with late-night eating habits exhibited higher intake of energy-dense, carbohydrate- and fat-rich foods, and had elevated body fat mass (20.66 ± 8.31 kg), percent body fat (32.95 ± 10.4%), and visceral fat levels (9.71 ± 4.78). Excessive screen time, especially during evening hours, is significantly associated with increased night eating frequency and poorer body composition among young adults. These findings emphasize the need for behavioural interventions targeting digital exposure, mindful eating, and meal timing to reduce the risk of lifestyle-related disorders in this age group.